Quality control of nuclear charcoals: Particle size effect and trapping mechanism - Duangjai Nacapricha (2018)
The efficiency of activated, impregnated charcoal for trapping radioiodine released from nuclear plants is expressed as a K value, measured by dosing a bed of charcoal with methyl iodide(I-131). K value measurements on commercial charcoals are often imprecise. A major source of this imprecision lies in the range of particle sizes that can exist in charcoals used for trapping. Charcoals impregnated with potassium iodide by spraying or by rotary evaporation have been graded by sieving, and the K value and other parameters of the main fractions have been measured. K values have been found to increase with decreasing particle size over the size range 6-12 BSS. Comparable trends have been observed for bed density, surface area, pore volume, saturation water content and impregnant distribution. K value precisions are significantly better for graded charcoal samples than for those selected randomly from an overall batch: hence uniform particle size is a requisite for precise quality control. The effect of ageing on the performance of KI-impregnated charcoals has been examined and some observations have been made on the mechanism of the reaction between methyl iodide and iodide ion on a carbon surface.